Inducing seed dispersal by generalist frugivores: A new technique to overcome dispersal limitation in restoration. Issue 12 (25th August 2020) - Silva, Wesley R.; Zaniratto, Cristiane P.; Ferreira, José O. V.; Rigacci, Eduardo D. B.; Oliveira, Jasmim F.; Morandi, Maria E. F.; Killing, Jéssica G.; Nemes, Larissa G.; Abreu, Laura B.
Abstract: Dispersal limitation severely impairs the trajectory of restoration, mainly due to the lack of seed vectors bringing seeds from nearby habitats; a role played by many frugivorous vertebrates that can be absent or reduced in restored or degraded sites. Here we propose a new technique named Induced Seed Dispersal, that amplifies the role that many generalist frugivores have in seed dispersal. It consists in the offering of seeds embedded in the pulp of commercial fruits or whole native fleshy fruits in feeders to generalist frugivores, which ingest the seeds and defecate them elsewhere. We set feeders in a restored site and monitored the visiting pattern of these frugivores with cameras‐traps. We also set seed traps to retrieve seeds dispersed by frugivores and offered around 1, 500 seeds of Cecropia hololeuca (Urticaceae) per week for 1 year. We recorded at least 24 generalist frugivore species of terrestrial mammals, bats and birds, which ingested/removed the seeds/fruits from the feeders. Seeds of C. hololeuca dispersed by marmosets were retrieved in the seed traps and germinated. We estimated a potential seed rain of more than 600 C. hololeuca seeds ha −1 mo −1 . Synthesis and applications . Our study demonstrates that this new technique can make use of generalist frugivores to assist restoration or regeneration into sites where seed dispersal is compromised by the lack of dispersers or limited seed arrival. Inducing seed dispersal by generalist frugivores is a low‐cost and easy‐managed technique that can be applied year‐round in restoration and forest enrichments at all scales. Abstract : Our study demonstrates that this new technique can make use of generalist frugivores to assist restoration or regeneration into sites where seed dispersal is compromised by the lack of dispersers or limited seed arrival. Inducing seed dispersal by generalist frugivores is a low‐cost and easy‐managed technique that can be applied year‐round in restoration and forest enrichments at all scales.